PELAYANAN PUBLIK DI KABUPATEN SUBANG (STUDI KASUS PELAYANAN UJI KIR DAN TRAYEK PADA DINAS PERHUBUNGAN KABUPATEN SUBANG) - Zaenal Hirawan (Jurnal Administrasi Publik, 2017)
This research was done based on service issues and the Route Permit Test KIR that where the level of reliability in the provision of services is still low, the institutions have not implemented a number of security they offer third party services routes and the extension of KIR test and other things. The method used in this research is descriptive method with qualitative approach. The results showed that the services are not reflected transparency. This is evident from the service charge is not yet open to the public. The creation of accountability and compliance with regulations regarding the issuance of a Route Permit and pass book KIR Test. Still not the creation of conditional means that the level of consistency less noticed by the government apparatus. From the other side that the public expects that the fast service, the cost can be reached and a clear time to process it. Conditions such as these cause the public service held by the government is not going well. Participatory still lack the services to encourage community participation in the implementation of public service with the aspirations, needs and expectations of society. Equal rights are still not the creation of the ministry that does not discriminate from the aspects of any particular tribe, race, religion, class, social status, and others. Judging from the number of people who do not get the right trajectory license in service and KIR test of the government. Still not the creation of a balance of rights and obligations of the ministry that considers the aspect of justice between providers and recipients of public services.